Cross country comparison of genetic diversity by merging microsatellite data from pigs - Ibeka, Cyril O., author; Whittier, Jack, advisor; Blackburn, Harvey, advisor; Chapman, Phillip, committee member (Colorado State University. Libraries, 2014)
The need to develop a comprehensive method to extend genetic diversity to a global level has never being more important given the increase in the amount of genetic information being generated within various countries using different genotyping procedures, hence the need to merge datasets. Merging also enables a country to compare the genetic diversity of its animals to other countries. Many genetic diversity studies have been limited either due to the use of manual merging techniques, which ignores the effect of different laboratories with different laboratory protocols and are obviously time consuming or due to allele size inconsistencies in the case of automated merging processes. Our objective was to develop a method that extends genetic diversity globally using inexpensive methods based on Bayesian approach. Thirty microsatellite markers were originally genotyped from 220 Brazilian pigs and thirty-five microsatellite markers were genotyped from 179 pigs from the United States. Fourteen microsatellite markers were common between pigs in both countries. However, twelve microsatellite markers with posterior probability greater than 0.550 were successfully merged using a Bayesian cluster method. GENALEX and FSTAT results showed that the Brazilian pigs were significantly different from the Chinese (P< 0.01667) and US (P < 0.01667) pigs but were genetically closer to the US breeds (0.25) than the Chinese breeds (0.42). Population structure results obtained from STRUCTURE software showed peaks at K = 2, 4, 13 and 15. STRUCTURE result with K = 4 showed evidence of geographic differentiation of breeds into Brazil, China and the United States. STRUCTURE result at K = 9 revealed evidence of admixture within countries. The Chinese pigs showed evidence of genetic differentiation within the breeds. Many Brazilian pigs are not unique pigs but are admixtures developed by crossing local pigs with commercial pigs. The genetic diversity of the US swine population may need to be increased to prevent loss of biodiversity in the event of disease outbreaks or natural disaster.
Keywords: animal genetic resources; pigs; genetic diversity; Bayesian methods